Analysis on the Effect of Sensor Views in Image Reconstruction Produced by Optical Tomography System Using Charge-Coupled Device - Jamaludin J.; Rahim R.A.; Fazul Rahiman M.H.; Mohd Rohani J. (Institute of Electrical and Electronics Engineers Inc., 2024)
Volume: 27 Issue: 4